Answer:
Explanation:
{−2x + 2y + 3z = 0
{−2x - y + z = −3 ←
{2x + 3y + 3z = 5 ←
2y + 4z = 2 ↷
{−2x + 2y + 3z = 0 ←
{−2x - y + z = −3
{2x + 3y + 3z = 5 ←
5y + 6z = 5 ↷
{5y + 6z = 5
{2y + 4z = 2
−⅖[5y + 6z = 5]
{−2y - 2⅖z = −2 >> New Temporary Equation
{2y + 4z = 2
____________
1⅗z = 0
___ _
1⅗ 1⅗
[Plug this back into both equations above to get the y-term of 1, then plugging both z-term and y-term into all three equations at the very top, will give you the x-term of 1];
;
I am joyous to assist you anytime.